(untitled) (Eurasian Journal of Ecology, 2018)
Natural area of the stone moroco Pseudorasboraparva (Temminck et Schlegel, 1846) ranges waters of the Amur watershed, Korea and Southeast Asia. This paper presents some results of investigation of its recent range in water bodies of the Syrdarya basin in borders of the Republic of Kazakhstan. This species was observed in many investigated sites of the main river as well as in several tributaries. Stone morocco was revealed in runny and stagnant waters. Habitual methods of fish biology and morphology investigations were applied to analyze samples from the Karashyk River. This population was chosen by ordinary living conditions for stone moroco in the whole basin. A method of pathologies investigation at morphological level namely index of unfavorable state evaluation was applied too. Maximal size of investigated samples was less than for the native and some alien populations. Fishes from 0 to 3 years old were presented in the Karashyk river. Some not significant abnormalities in external morphology of liver and kidneys of the samples of stone morocowere revealed, but common index of unfavorable state (IUS) fitted to relatively favorable conditions. The stone moroco often is a pest for indigenous fishes, but sometimes it can be used for control of water larvae of bloodsucking mosquito in water bodies with unstable water regimen. Key words: stone moroco, alien, introduction, morphology, pathology, Syrdarya, age, population.